“Quitlink”—A Randomized Controlled Trial of Peer Worker Facilitated Quitline Support for Smokers Receiving Mental Health Services: Study Protocol - Baker, Amanda L.; Borland, Ron; Bonevski, Billie; Segan, Catherine; Turner, Alyna; Brophy, Lisa; McCarter, Kristen; Kelly, Peter J.; Williams, Jill M.; Baird, Donita; Attia, John; Sweeney, Rohan; et al. (Frontiers in Psychiatry, 2019)
Introduction Although smokers with severe mental illnesses (SSMI) make quit attempts at comparable levels to other smokers, fewer are successful in achieving smoking cessation. Specialized smoking cessation treatments targeting their needs can be effective but have not been widely disseminated. Telephone delivered interventions, including by quitlines, show promise. However, few SSMI contact quitlines and few are referred to them by health professionals. Mental health peer workers can potentially play an important role in supporting smoking cessation. This study will apply a pragmatic model using peer workers to engage SSMI with a customised quitline service, forming the ‘Quitlink’ intervention. Methods A multi-centre prospective, cluster-randomised, open, blinded endpoint (PROBE) trial. Over 3 years, 382 smokers will be recruited from mental health services in Victoria, Australia. Following completion of baseline assessment, a brief intervention will be delivered by a peer worker. Participants will then be randomly allocated either to no further intervention, or to be referred and contacted by the Victorian Quitline and offered a targeted eight-week cognitive behavioural intervention along with nicotine replacement therapy (NRT). Follow-up measures will be administered at 2-, 5- and 8-months post-baseline. The primary outcome is 6 months continuous abstinence from end of treatment with biochemical verification. Secondary outcomes include 7-day point prevalence abstinence from smoking, increased quit attempts, and reductions in cigarettes per day, cravings and withdrawal, mental health symptoms, and other substance use, and improvements in quality of life. We will use a generalised linear mixed model (linear regression for continuous outcomes and logistic regression for dichotomous outcomes) to handle clustering and the repeated measures at baseline, 2-, 5- and 8-months; individuals will be modelled as random effects, cluster as a random effect, and group assignment as a fixed effect. Discussion This is the first rigorously designed RCT to evaluate a specialized quitline intervention accompanied by NRT among SSMI. The study will apply a pragmatic model to link SSMI to the Quitline, using peer workers, with the potential for wide dissemination.